Study, Design and Improve Production Line Layout using Material Flows (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Companies search for production bottlenecks in an effort to get a competitive edge in the market. Automated production lines must be introduced and innovated for reasons related to productivity, quality, and manpower shortages. A production line is essentially defined as a system of accuracy, fluidity, and speed. New technologies have also prompted manufacturing lines to continually innovate and speed up, this article discusses innovation and addresses the challenge of creating a whole new layout for a new manufacturing line in the food business. This research aimed to develop the best possible production line arrangement in pre-selected manufacturing regions. Making the best possible use of the area allotted for production is crucial for every modern business.